2019
DOI: 10.1002/csr.1716
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and environmental social governance disclosure: A meta‐analytical review

Abstract: This paper provides, to the best of the authors' knowledge, the first meta-analysis of evidence about the influence of the corporate governance on environmental, social, and governance (ESG) disclosure, in a setting where the disclosure of information is voluntary but not discretionary. We apply meta-analysis to a sample of 24 empirical studies to clarify the relationship of board size, board independence, women on board, number of board meeting, CEO duality, and company ownership with ESG disclosure. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
204
4
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(234 citation statements)
references
References 85 publications
17
204
4
9
Order By: Relevance
“…Furthermore, compared with companies that had not corrected major deficiencies, those that had corrected major deficiencies made significant improvement in the structure of the board of directors, audit committees, and senior management. The literature confirms that good firm governance, diversity of the board of directors, and improvement in the educational qualifications of senior management can effectively restrain a company's environmental pollution, improve its environmental information disclosure level, and promote the true fulfillment of the company's environmental commitments [23,25,28,30]. Therefore, high-quality internal control through improvement of firm governance can help reduce the self-interested motivation of managers and controlling shareholders, maximize the protection of the rights and interests of various stakeholders, and provide reasonable assurance of reliable firm environmental reporting.…”
Section: Theoretical Analysis and Research Questionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, compared with companies that had not corrected major deficiencies, those that had corrected major deficiencies made significant improvement in the structure of the board of directors, audit committees, and senior management. The literature confirms that good firm governance, diversity of the board of directors, and improvement in the educational qualifications of senior management can effectively restrain a company's environmental pollution, improve its environmental information disclosure level, and promote the true fulfillment of the company's environmental commitments [23,25,28,30]. Therefore, high-quality internal control through improvement of firm governance can help reduce the self-interested motivation of managers and controlling shareholders, maximize the protection of the rights and interests of various stakeholders, and provide reasonable assurance of reliable firm environmental reporting.…”
Section: Theoretical Analysis and Research Questionmentioning
confidence: 80%
“…Their results revealed that the age of the youngest director has a negative effect on environmental disclosure, while in contrast independent directors and the presence of lead independent directors strengthen the decision to develop environmental disclosures. Furthermore, Lagasio and Cucari [28] found that board independence, board size and female director status significantly improved environmental, social, and governance (ESG) voluntary disclosures; whereas board ownership and chief executive officer (CEO) duality did not. Pucheta-Martínez and López-Zamora [29] analyze the role performed by representatives of institutional investors in environmental reporting in Spain.…”
Section: Firm Governancementioning
confidence: 99%
“…Hollindale et al (2019) results stressed instead the importance of having multiple female directors for increasing the quality of GHG emission-related disclosure in annual and sustainability reports. Cucari et al (2018), conversely, reported a negative relationship between women on the board and ESG disclosure, suggesting that the presence of women directors is more driven by regulatory pressures. On balance, this body of research appears to point to women directors being associated with higher ESG and related disclosure.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 93%
“…Following the studies on CSR in general, some researchers found that women have a more protective attitude towards the environment in particular (Wehrmeyer & McNeil, 2000) and are more likely than males to be ecologically conscious (Park, Choi, & Kim, 2012). Related research shows that boards with a higher proportion of women directors had higher environmental performance (Kassinis et al, 2016;Li et al, 2017;Lu & Herremans, 2019;Post et al, 2015;Walls et al, 2012) and higher levels and quality of environmental reporting (Rao et al, 2012;Liao et al, 2015;Ben-Amar et al, 2017;Lagasio & Cucari, 2019;Bravo and Reguera-Alvarado, 2019). These relationships are found in non-U.S. countries as well, such as in Spain in terms of GRI reporting (Fuente et al, 2017) and Australia in terms of corporate sustainability activities (Nadeem et al, 2017).…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…For instance, “the EU policy for sustainable finance is not only a policy in the EU (the third polluter of the world responsible for 10% of the emissions), but thanks to the EU political leadership in the area may become a policy for the world, or at least the world biggest economies Nava (forthcoming). New rules are expected to bring about more long‐term focus in corporate governance and address a number of governance shortcomings (Brogi & Lagasio, ; Cucari, Esposito De Falco, & Orlando, ; Lagasio & Cucari, ; Lo & Kwan, ). For instance, the question of how compatible ESG criteria are with corporate financial performance has remained central in the debate for practitioners and academics alike for more than 40 years (Friede, Busch, & Bassen, ).…”
Section: Background and Focus Of The Special Issuementioning
confidence: 99%